Prognostic value of programmed cell death ligand-1 expression in ovarian cancer: an updated meta-analysis - Jinlan Piao; Hyun Ji Lim; Maria Lee (Korean Society of Obstetrics and Gynecology, 2020)
ObjectiveTo investigate the prognostic significance of programmed cell death ligand-1 (PD-L1) in ovarian cancer.MethodsPubMed, Embase, and Cochrane Library databases were searched to identify studies that examined the prognostic significance of immunohistochemically assessed PD-L1 expression in histologically confirmed ovarian cancer. Eleven studies on PD-L1 expression involving 1,296 patients with ovarian cancer were included in this meta-analysis. Pooled hazard ratios (HRs) with corresponding 95% confidence intervals (CIs) were analyzed. Relationship between PD-L1 expression, and overall survival (OS) or progression-free survival (PFS) among patients with ovarian cancer was assessed. Subgroup analysis was performed based on the race, histologic type, and tumor International Federation of Gynecology and Obstetrics stage to evaluate the source of heterogeneity. Begg's Funnel plot and Egger's linear test were used to evaluate publication bias. Random-effects model was implemented when significant between-study heterogeneity (I2>50%) was observed.ResultsWe found no correlation between PD-L1 expression, and OS (HR, 1.13; 95% CI, 0.95-1.36; I2=78%) or PFS (HR, 1.07; 95% CI, 0.88-1.30; I2=75%) in ovarian cancer. Subgroup analyses showed that higher PD-L1 expression was associated with poor OS in non-Asian patients with ovarian cancer (HR, 1.26; 95% CI, 1.07-1.481; I2=59%). We found that upregulated PD-L1 expression to be a positive predictor for OS in serous ovarian cancer (HR, 0.98; 95% CI, 0.76-1.26; I2=74%) and a negative predictor for OS in non-serous ovarian cancer (HR, 1.29; 95% CI, 1.03-1.61; I2=64%) Furthermore, high PD-L1 expression was found to be a negative predictor for PFS of patients with non-serous ovarian cancer (HR, 1.12; 95% CI, 0.96-1.29; I2=37%).ConclusionOur meta-analysis suggests that PD-L1 expression is not associated with patient risk for ovarian cancer.